Inactivity of Stat3 in sensory and non-sensory cells of the mature cochlea - Bieniussa, L.; Stolte, C.; Arampatzi, P.; Engert, J.; Völker, J.; Hagen, R.; Hackenberg, S.; Rak, K. (Frontiers in Molecular Neuroscience, 2024)
Signal transducer and activator of transcription 3 (Stat3) plays a role in various cellular processes such as differentiation, inflammation, cell survival and microtubule dynamics, depending on the cell type and the activated signaling pathway. Stat3 is highly expressed in the hair cells and supporting cells of the cochlea and is essential for the differentiation of mouse hair cells in the early embryonic stage. However, it is unclear how Stat3 contributes to the correct function of cells in the organ of Corti postnatally. To investigate this, an inducible Cre/loxp system was used to knock out Stat3 in either the outer hair cells or the supporting cells. The results showed that the absence of Stat3 in either the outer hair cells or the supporting cells resulted in hearing loss without altering the morphology of the organ of Corti. Molecular analysis of the outer hair cells revealed an inflammatory process with increased cytokine production and upregulation of the NF-kB pathway. However, the absence of Stat3 in the supporting cells resulted in reduced microtubule stability. In conclusion, Stat3 is a critical protein for the sensory epithelium of the cochlea and hearing and functions in a cell and function-specific manner.